Fintech and responsibility: Buy-now-pay-later arrangements. Issue 3 (August 2022) - Gerrans, Paul; Baur, Dirk G; Lavagna-Slater, Shane
Buy-now-pay-later (BNPL) arrangements have rapidly emerged as a short-term debt option, and like other innovative and disruptive Fintech, challenge existing regulation. BNPL arrangements avoided prescribed 'responsible lending' legislative obligations, which applied to similar short-term credit products. Instead, BNPL relies on 'responsible spending' in providing a potentially cheaper option than alternatives such as credit cards. We describe the interplay of regulation and responsibility with BNPL. A survey investigates whether a key demographic (young adults) have an appetite or skill for responsible use. We analyse the preference for BNPL relative to credit cards and the role of financial literacy and traits including propensity to plan and save. The findings suggest that financial literacy reduces perceived BNPL benefits and that lower financial literacy is associated with more benefits and less risks. JEL Classification:G53, D14, G51, G41, G18